Effect of physical parameters on the decolorization of multiple synthetic textile dyes by bacteria recovered from dye contaminated soil and water - Kamal, Mostafa; Bhuiyan, Dr. Mohammad Nazrul Islam (BRAC University, 2018)
This thesis report is submitted in partial fulfilment of the requirement for the degree of Master of Science in Biotechnology, 2018.